School and society : historical and contemporary perspectives - Tozer, Steven; Violas, Paul C.; Senese, Guy B. (Boston : McGraw-Hill, 2002)
This book gives a balanced look at historical and contemporary education and tells the engaging story of the evolution of American education, showing how and why certain school-society issues first arose in this country and how and why they changed over time.
Includes bibliographical references and index.
Keywords: Educational sociology -- United States; Education -- History -- United States